Application of response surface method to energy and exergy analyses of the ohmic heating dryer for sour orange juice. (15th October 2020) - Vahedi Torshizi, Mohammad; Azadbakht, Mohsen; Kashaninejad, Mahdi
Graphical abstract: Highlights: By increasing the voltage gradient value, the energy efficiency and exergy amount have increased. With increasing percentage weight loss, energy efficiency decreased and exergy efficiency have increased. Exergy loss has been increased with increasing process time and percentage weight loss. The precision level (R2) of the response surface method was good for modeling and close to 1. The combined optimum hot pressing parameters were predicted and validated using RSM. Abstract: An ohmic heating system was constructed, three input voltage gradients 8.33, 10.83, 13.33 V/cm and three weight loss percentage points of the sample 10, 20 and 30% compared to the total weight, were selected for the heating process. During the thermal process, the energy efficiency, the exergy efficiency, the exergy loss, and the potential improvement over time, as well as reaching the desired weight were examined. The results were analyzed using the response surface method. According to the results, the energy efficiency decreases by increasing the process time, but the exergy loss and exergy efficiency increase by increasing the process time. First for the improvement potential amount was initially upward and then downward. In general, the voltage gradient and the weight loss percentage have significant effects on the process time, the energy efficiency, the exergy efficiency, the exergy loss and the improvement potential. The maximum and minimum amounts for energy efficiency were 91.68 and 50.31% in voltage gradient 13.33 V/cm and 8.33 V/cm and weight loss percentage 10 and 30% respectively, also for exery efficiency, the maximum amount was 59.46% in 13.33 V/cm and 30% and minimum amount was 31.56% in 8.33 V/cm and 10% weight loss percentage. Finally the maximum amount for exergy loss and improvement potential were 6.3 and 5.563 kW that have been obtained in 8.33 V/cm and 30% weight loss percentage and minimum amount for this factors were 2.4 and 1.569 kW in 13.33 V/cm and 10% weight loss percentage respectively. The best model for the energy efficiency, the exergy efficiency, the improvement potential and the exergy loss was selected as the linear and interactions models, the second-order model versus the two factors, the average and linear model, and the second-order model versus the two factors, respectively. Additionally, R 2 value was very good for the data predicted.